Target-based anticancer indole derivatives and insight into structure‒activity relationship: A mechanistic review update (2018–2021) - Ashima Dhiman; Rupam Sharma; Rajesh K. Singh (Acta Pharmaceutica Sinica B, 2022)
Cancer, which is the uncontrolled growth of cells, is the second leading cause of death after heart disease. Targeting drugs, especially to specific genes and proteins involved in growth and survival of cancer cells, is the prime need of research world-wide. Indole moiety, which is a combination of aromatic-heterocyclic compounds, is a constructive scaffold for the development of novel leads. Owing to its bioavailability, high unique chemical properties and significant pharmacological behaviours, indole is considered as the most inquisitive scaffold for anticancer drug research. This is illustrated by the fact that the U.S. Food and Drug Administration (FDA) has recently approved several indole-based anticancer agents such as panobinostat, alectinib, sunitinib, osimertinib, anlotinib and nintedanib for clinical use. Furthermore, hundreds of studies on the synthesis and activity of the indole ring have been published in the last three years. Taking into account the facts stated above, we have presented the most recent advances in medicinal chemistry of indole derivatives, encompassing hot articles published between 2018 and 2021 in anticancer drug research. The recent advances made towards the synthesis of promising indole-based anticancer compounds that may act via various targets such as topoisomerase, tubulin, apoptosis, aromatase, kinases, etc., have been discussed. This review also summarizes some of the recent efficient green chemical synthesis for indole rings using various catalysts for the period during 2018–2021. The review also covers the synthesis, structure‒activity relationship, and mechanism by which these leads have demonstrated improved and promising anticancer activity. Indole molecules under clinical and preclinical stages are classified into groups based on their cancer targets and presented in tabular form, along with their mechanism of action. The goal of this review article is to point the way for medicinal chemists to design and develop effective indole-based anticancer agents.